ANALISIS SUSTAINABLE COMPETITIVE ADVANTAGE FESTIVAL BANDENG SEBAGAI DAYA TARIK WISATA BUDAYA DI RAWA BELONG, JAKARTA BARAT - Teresia; Yudhiet Fajar Dewantara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Rawa Belong Bandeng Festival is an annual cultural festival rooted in the acculturation of Betawi and Chinese ethnicities, held in West Jakarta to welcome the Chinese New Year and grounded in the "Nganter Bandeng" tradition that has existed since the 1960s. Despite its significant cultural potential, the festival continues to face governance challenges and has not been academically examined using a systematic strategic framework. This study aims to identify the resources and capabilities of the Rawa Belong Bandeng Festival as a cultural tourism attraction and to analyze its Sustainable Competitive Advantage (SCA) position based on the VRIO framework (Value, Rarity, Imitability, Organization). This research employs a descriptive qualitative approach through in-depth interviews with nine informants, participant observation, and documentation, with data analysis using the Miles, Huberman, and Saldaña (2014) model operationalized through VRIO scoring. The findings identify six indicators: Nganter Bandeng Tradition, Cultural Arts and Performances, Local Cultural Uniqueness, Inter-Cultural Acculturation, Atmosphere and Area Identity, and Organizing Body Capability. Overall, the Rawa Belong Bandeng Festival occupies an Unused Competitive Advantage position with an average score of 30.5 out of 36 (85%). Five resource indicators are positioned at Unused Competitive Advantage (81–92%), while the Organizing Body Capability sits at Competitive Parity (61%). The Organization dimension consistently emerges as the critical point. The study recommends establishing a permanent promotion division, registering the Nganter Bandeng tradition as Intangible Cultural Heritage, extending preparation time to three or four months, and strengthening internal organizational capability to drive transformation toward Sustainable Competitive Advantage.